Bridging tradition and modernity: exploring patutan (the modal system) in Balinese music through the hybrid composition ‘cane’ - Kartawan, I Made; Putra, I Made Dwi Andika; Hartini, Ni Putu (International Journal of Visual and Performing Arts, 2024)
This paper examines how the composer integrates traditional Balinese gamelan elements with Western musical concepts in the creation of the piece "Cane," focusing on two main aspects: the creative process and aesthetic analysis. Several strategies are employed, such as adopting, borrowing, transforming, elaborating, ornamenting, and combining musical elements from various genres and cultural traditions. The hybrid work "Cane" exemplifies this approach by blending motifs, patterns, and ornamentation from both Balinese and Western music. Additionally, the piece incorporates the processing of patutan/patet (modal system) from the Semar Pagulingan Saih Pitu gamelan ensemble. Rooted in research and experimentation, "Cane" is structured into five distinct parts, each utilizing one or more of these strategies. The music emphasizes melodic development intertwined with rhythmic, dynamic, and tempo variations. In the context of hybridization, the combination of musical elements includes: (1) Balinese traditions such as kekenyongan, nyongcag, ngempyung, and kekilitan motifs, and (2) Western elements like unison, harmony, dissonance, polyphony, and imitation